Bibliometric study on ostomy and wounds (Research, Society and Development, 2021)
Objective: Bibliometric study that aimed to describe the characteristics of scientific production related to wounds and ostomies. Methodology: The terms injuries and injuries and ostomy were used in the data collection that was carried out on October 6, 2020, in the Web of Science (WoS) database. The variables observed were: year of publication, authors, country, language, institutions, journals and research areas. Results: Evidenced 52 indexes in a period of twenty-seven years (1993 to 2020). Of the publications, 71% were articles from the United States of America (USA), Brazil does not appear in the ranking of publications, 100% publications were in English; all were original articles, the author who publishes the most is in the USA. Conclusion: We conclude that the scientific production was higher in 2016, the study also shows the involvement of nursing in the subject, so it is clear the need for more scientific involvement of Brazilian nursing with the subject so that there is a progressive growth on the subject in the country.